A Universal In Situ Cross‐Linking Strategy Enables Orthogonal Processing of Full‐Color Organic Microlaser Arrays. (30th April 2021) - Fan, Yuqing; Zhang, Chunhuan; Du, Yuxiang; Qiao, Chan; Wang, Kang; Hou, Yue; Yao, Jiannian; Zhao, Yong Sheng
Abstract: Large‐scale red, green, and blue (RGB) microlaser arrays capable of exhibiting full‐color laser emissions are urgently desired for high‐performance flat‐panel laser displays. With excellent solution processability and optoelectronic properties, organic materials are promising candidates for full‐color microlasers; however, the heterogeneous integration of full‐color microlasers remains a challenge due to their poor solution stability to withstand multistage solution processing. Here, a robust in situ cross‐linking strategy is proposed to enable orthogonal processing of organic microlasers to heterogeneously integrate large‐scale full‐color organic microlaser arrays. The organic microlasers with controlled physical dimensions and spatial locations are fabricated with an electron beam (e‐beam) induced in situ polymerization reaction. Profiting from enhanced orthogonality of microlasers, large‐scale pixelated RGB microlaser arrays are monolithically integrated through successive e‐beam patterning processes. Laser emissions in the RGB microlaser pixels cover a color gamut 41% larger than the standard RGB space, with which flexible full‐color organic laser display patterns with a resolution of 254 dpi on a centimeter scale is obtained. The scalable heterogeneous integration platform reported in this work will pave a new avenue for the efficient construction of large‐scale high‐performance organic integrated optoelectronic devices. Abstract : A universal and robust in situ cross‐linking strategy is developed to endow organic microstructures with high orthogonality for scalable monolithic integration of red, green, and blue organic microlaser arrays. The resulting microlaser arrays with controllable physical dimensions and spatial locations exhibit intense full‐color tunable laser emissions, enabling to be utilized to develop high‐performance self‐emissive display panels.